Responses of stream zooplankton diversity metrics to eutrophication and temporal environmental variability in agricultural catchments - Gutierrez, Marìa Florencia (2020)
Eutrophication of rivers and streams in agricultural lands is one of the main threats for biodiversity and ecosystem functions. This study was focused on seven subtropical streams where agriculture is the predominant land use. We tested the hypothesis that (i) eutrophication causes a decrease in taxonomic and functional diversity of zooplankton, leading to potential consequences for the ecosystem integrity. Furthermore, given that the temporal variability in the environmental conditions of each stream may influence the species sorting mechanisms, we also hypothesized that (ii) streams with higher temporal environmental variability have greater taxonomic and functional alpha (α) and temporal beta (βt) diversity measures regardless of the trophic state. Thus, we characterized the streams according to their trophic state and analyzed the zooplankton composition, α and βt by using taxonomic and functional perspectives. We found differences in the zooplankton composition between mesotrophic and eutrophic streams. However, eutrophic streams supported similar taxonomic and functional α diversity and similar taxonomic βt diversity to mesotrophic ones. These results were mainly explained by the occurrence of rare species occupying different temporal niches in eutrophic systems. On the contrary, functional βt diversity was lower in the eutrophic streams, being nestedness the ecological mechanisms underlying the variability in the zooplankton functional groups. Streams with higher temporal environmental variability supported greater α taxonomic diversity. However, the βt diversity metrics showed no correlation with the environmental variability, suggesting that the environmental filters of the studied systems were the overriding determinants of species turnover. Our study suggests that both taxonomic and functional perspectives should be considered to improve our knowledge on the biotic responses to environmental changes. Also, among all metrics analyzed on the zooplankton community, functional βt diversity was the most sensitive indicator of the eutrophication impact.